Enhancing the dissolution rate of mefenamic acid with solid dispersion system using avicel PH-101 - Widyasari Putranti; Lina Widiyastuti; Fitri Ulfani (Pharmaciana, 2019)
Mefenamic acid, based on the Biopharmaceutics Classification System (BCS), is a class II drug that has high permeability but low water solubility. To improve its intrinsic dissolution rate, it is usually combined with a hydrophilic and porous drug carrier like Avicel to create a solid dispersion. This study aimed to enhance the intrinsic dissolution rate of mefenamic acid using a solid dispersion with Avicel PH-101. The test of intrinsic dissolution rate involved a rotational speed of 60 rpm and CO2-free water with a temperature of 37°C as a medium. The interaction of mefenamic acid and Avicel PH-101 was analyzed with FTIR and DSC spectroscopy. The test results showed that the intrinsic dissolution rates (in mg.cm-2.minute-1) of three replications of mefenamic acid, Solid Dispersion of Mefenamic Acid and Avicel PH-101 (SDMA) with 1:1 ratio, SDMA with 1:2 ratio, Physical Mixture of Mefenamic Acid and Avicel PH-101 (PMMA) with 1:1 ratio, and PMMA with 1:2 ratio were (8.0x10-4 ± 3.0x10-4), (38.0x10-4 ± 3.0x10-4), (67.0x10-4 ± 10.0x10-4), (20.0x10-4 ± 6.0x10-4), and (44.0x10-4 ± 14.0x10-4), respectively. The interaction between mefenamic acid and Avicel PH-101 created a hydrogen bonding, as evidenced by the shift in the peaks of FTIR spectra. Based on the DSC thermogram, the mefenamic acid-Avicel PH-101 interaction shifted the steep peak on the curve of mefenamic acid slightly. Avicel PH-101 in this solid dispersion can increase the intrinsic dissolution rate of mefenamic acid through hydrogen bonding instead of decreasing its crystalline structure into an amorphous from.